2022
DOI: 10.22219/jamanika.v2i04.23808
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Product Quality on Purchase Decision Mediated by Brand Image in Zara Women’s Bag Consumers

Abstract: This study examines the effect of product quality on purchasing decisions with the brand image as a mediating variable. The research was conducted in Tunjungan Plaza, Galaxy Mall, and Pakuwon Mall with a total sample of 150 respondents of Zara Women’s consumers. The data collection technique in this study used an online questionnaire. The data analysis technique in this study uses partial least squares using Smart PLS software. The results of the partial least squares (PLS) analysis show that product quality h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…Based on the findings of the SmartPLS analysis, it can be concluded that the product quality variable has a positive and statistically significant impact on purchase decisions. This is in line with research conducted by Arifin et al (2022) who researched product quality influences on purchasing decisions in a study of 150 Zara Women consumer respondents shopping centers in Tunjungan Plaza, Galaxy Mall, and Pakuwon Mall in Surabaya, where it was found that product quality had a positive and significant effect on purchasing decisions. In addition, the results of this study prove that durability and reliability indicators have an important role in consumers' decisions to buy 3Second fashion products.…”
Section: B Hypothesis Testingsupporting
confidence: 89%
See 1 more Smart Citation
“…Based on the findings of the SmartPLS analysis, it can be concluded that the product quality variable has a positive and statistically significant impact on purchase decisions. This is in line with research conducted by Arifin et al (2022) who researched product quality influences on purchasing decisions in a study of 150 Zara Women consumer respondents shopping centers in Tunjungan Plaza, Galaxy Mall, and Pakuwon Mall in Surabaya, where it was found that product quality had a positive and significant effect on purchasing decisions. In addition, the results of this study prove that durability and reliability indicators have an important role in consumers' decisions to buy 3Second fashion products.…”
Section: B Hypothesis Testingsupporting
confidence: 89%
“…One factor that is thought to mediate the influence of product quality on this purchase decision is brand image (Arifin et al, 2022;Nuraini & Maftukhah, 2015) Brand image, or the perception associated with a company's name, term, symbol, sign, and design, serves to differentiate its products from competitors (Aulia & Briliana, 2017). This image can be cultivated using various media owned by the company and is enduring, delivering a message through visual media, symbols, atmosphere, and events.…”
Section: Introductionmentioning
confidence: 99%
“…The brand image also helps a product to get consumers because if the brand image that the product has is very strong, it will certainly result in brand perceptions that exist in consumers being good so that consumers feel confident in making product purchasing decisions and so that brand image also acts as a mediator to improve the relationship between product quality and purchasing decisions. In line with research conducted by Arifin et al (2022) proves that product quality influences purchasing decisions through brand image as a mediating variable, while in other research also from Saraswati & Giantari (2022) proves that brand image mediates positively and significantly the effect of product quality on purchasing decisions. It strengthens the role of brand image as a variable that mediates positively and significantly the effect of product quality on purchasing decisions.…”
Section: The Effect Of Product Quality On Purchasing Decisions Mediat...supporting
confidence: 82%
“…In line with research conducted by Erlitna & Soesanto (2018), they proved that product quality positively and significantly affects brand image. Then, other research from Arifin et al (2022) strengthens the evidence that product quality positively and significantly affects brand image. It makes it clear that the better and higher quality of a product can encourage the creation of a positive image perceived by consumers regarding the brand or product offered.…”
Section: The Effect Of Product Quality and Brand Imagementioning
confidence: 74%
“…Keputusan pembelian dipengaruhi oleh beberapa faktor, perusahaan dituntut untuk selalu bersaing dan menarik perhatian konsumen. Ada beberapa faktor yang dapat mempengaruhi keputusan pembelian, diantaranya kualitas produk, kualitas pelayanan dan juga citra merek (Andrianto & Fianto, 2020;Arifin et al, 2022;Ma'arif & Budiarti, 2022).…”
Section: Pendahuluanunclassified